Politics of Translation of Kalidasa’s Sakuntalam into Malayalam: A Paratextual Study of the “First” Translation into Malayalam - Muraleedharan, Divya (South Asian Journal of Social Sciences and Humanities, 2021)
The paper attempts to understand the politics involved in the first translations of Sakuntalam into Malayalam. Prior to the genre of drama which was a late development, visual art performances like Kathakali, Koothu, Thullal, etc were the objects of appreciation and literary involvement of the Malyalaee audience. The inception of the Sangeetanatakas into the Kerala land brought in many changes in the aesthetics of the Malayalee literati. With the translation of Sakuntalam into Malayalam, there was a revoked interest in the literary interest of the Malayalee audience. With numerous translations of Sakuntalam into Malayalam, some within the same time frame, there emerged a contestation in which work to be considered as the first translation and who was the author to first translate the globally acclaimed Sanskrit text into Malayalam. In this context of the contestation and debates existing around the first translations and the ‘ascribed” first translation the paper examines the politics by employing paratextual study of the translations.